Defining the latent phase of labour: is it important? - Hundley, Vanora A.; Way, Susan; Cheyne, Helen; Janssen, Patricia; Gross, Mechthild; Spiby, Helen (Royal College of Midwives, 2017)
Background and rationale. The latent phase of labour is recognised as a period of uncertainty for women and midwives. There is evidence from the literature of considerable variation in labour definitions and practice. Stimulated by discussion at an international maternity research conference, the authors set out to explore opinions regarding the need for labour-stage definitions. Aim. To identify health professionals’ views on the need for a definition of the onset and the end of the latent phase of labour. Methods. This was an opportunistic, semi-structured, online survey of attendees at a maternity care research conference, which included midwives, other clinicians, academics, advocates and user representatives. Attendees (approximately 100) were invited to participate through a single email invitation sent by the conference committee and containing a link to the survey. Consent was sought on the landing page. Ethical approval was obtained from Bournemouth University’s research ethics committee. Quantitative questions were analysed using simple descriptive statistics using IBM SPSS Statistics Version 24. Open questions were analysed using content analysis and where participants gave a more detailed answer, these were analysed using a thematic approach. Findings. Participants in the survey (n=21) came from 12 countries. Most of the participants thought that there was a need to define the onset of the latent phase (n=15, 71%). Common characteristics were cited, but the main theme in the open comments referred to the importance of women’s perceptions of labour onset. Most participants (n = 18, 86%) thought that there was a need to define the end of the latent phase. This was felt necessary because current practice within facilities is usually dictated by a definition. The characteristics suggested were also not unexpected and there was some consensus; but the degree of cervical dilatation that signified the end of the latent phase varied among participants. There was significant debate about whether a prolonged latent phase was important; for example, was it associated with adverse consequences. Most participants thought it was important (n=15, 71%), but comments indicated that the reasons for this were complex. Themes included the value that women attached to knowing the duration of labour and the need to support women in the latent phase. Implications for practice. The findings from this small, opportunistic survey reflect the current debate within the maternal health community regarding the latent phase of labour. There is a need for more clarity around latent phase labour (in terms of both the definition and the support offered) if midwives are to provide care that is both woman centred and evidence-based. The findings will inform the development of a larger survey to explore attitudes towards labour definitions.